2020
DOI: 10.3390/nu12082271
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Determination of 25(OH) Vitamin D and 3-Epi25(OH)D3 in Breastmilk and Maternal- and Infant Plasma during Breastfeeding

Abstract: Vitamin D deficiency in pregnant women and their offspring may result in unfavorable health outcomes for both mother and infant. A 25hydroxyvitamin D (25(OH)D) level of at least 75 nmol/L is recommended by the Endocrine Society. Validated, automated sample preparation and liquid chromatography-tandem mass spectrometry (LC-MS/MS) methods were used to determine the vitamin D metabolites status in mother-infant pairs. Detection of 3-Epi25(OH)D3 prevented overestimation of 25(OH)D3 and misclassification of vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
0
11
1
Order By: Relevance
“…LLE 25(OH)D 3 ng/mL 24,25(OH) 2 D 3 Tear fluid [ 60 ] 35 μL from each eye 1. Extraction 25(OH)D 3 ng/mL Human milk [ 80 87 ] 200 μL–10 mL 1. Protein precipitation or D 3 ng/mL D 2 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LLE 25(OH)D 3 ng/mL 24,25(OH) 2 D 3 Tear fluid [ 60 ] 35 μL from each eye 1. Extraction 25(OH)D 3 ng/mL Human milk [ 80 87 ] 200 μL–10 mL 1. Protein precipitation or D 3 ng/mL D 2 1.…”
Section: Discussionmentioning
confidence: 99%
“…A fully automated sample preparation method was introduced by Gjerde et al, to measure 25(OH)D 2 , 3β-25(OH)D 3 and 3α-25(OH)D 3 [ 87 ]. A robotic autosampler was used to prepare the samples for analysis.…”
Section: Sample Preparation Of Alternative/non-conventional Biologica...mentioning
confidence: 99%
“…For all of these reasons, VD deficiency in infants and toddlers can be considered a frequent problem even in healthy subjects, with a prevalence ranging from 12% to 40% [ 51 ]. VD deficiency could represent a potential problem in infants exclusively breastfed by mothers having VD intakes of 400 IU/day, the amount normally assumed during pregnancy [ 40 ], and who do not receive direct and proper supplementation, as shown by a Norwegian study, which found a prevalence of 31% of VD deficiency in a population of 52 infants at 3 months of life, compared with a prevalence of 13% in their mothers at the same time [ 52 ]. VD deficiency can impact the quality of life of the child and particularly of the infant in the short and long term, and VD supplementation has been identified as a necessary and effective instrument for preventing VD deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…This Special Issue presents a compendium of excellent observational and interventional clinical studies regarding vitamin D. The high frequency of vitamin D insufficiency or deficiency among adults and the elderly [10], but also among mothers and their infants and in breastmilk [11], are underlined. Although vitamin D 3 production decreases with age, the significant role of outdoor sun exposure to increase serum vitamin D 3 concentrations in vivo in younger and older adults is demonstrated [12], and the barriers towards sun exposure and the potential improvement strategies to promote safe sun exposure to produce an optimal level of vitamin D are discussed [13].…”
mentioning
confidence: 99%
“…Although vitamin D 3 production decreases with age, the significant role of outdoor sun exposure to increase serum vitamin D 3 concentrations in vivo in younger and older adults is demonstrated [12], and the barriers towards sun exposure and the potential improvement strategies to promote safe sun exposure to produce an optimal level of vitamin D are discussed [13]. Regarding 25OHD assessment, it is specified that the detection of 3-Epi25(OH)D 3 using liquid chromatography-tandem mass spectrometry prevents the overestimation of 25OHD and misclassification of vitamin D status [11]. Interventional studies showed no effect of cholecalciferol on body weight reduction in obese children participating in a weight management program [14], or on bone mineral density in children with hypercalciuria [15].…”
mentioning
confidence: 99%